KONSEP KAFA’AH PERSPEKTIF KITAB IBANAT AL-AHKAM - Misbachul Fitri, Abd. Basit; Nafi’ah, Siti (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Kafa'ah in linguistic terms is المساوة والمماثالة which means balance and equal balance, while in terms it is equality between husband and wife in perfection. Kafa'ah is a factor that can encourage the creation of happiness between husband and wife and also reduce the chances of domestic conflict arising and ensure the safety of a woman from failure in building a household. Shaykh Abu 'Abdillah Al'alussy in the book Ibanat al-Ahkam provides an understanding that kafa'ah is a matter of religion. Because marriage is a religious order and is worth worship. With a religion, a person is expected to be able to carry out the teachings of his religion well. Meanwhile, other kafa'ah factors, namely lineage, wealth, employment, independence status are supporting measures. It was also emphasized that apart from religion, nowadays kafa'ah is also seen in terms of personal quality, level of intellectual intelligence and level of education, in this way we are able to bring a more contemporary concept that is able to meet the needs of the times.